Assessment and management of amputations distal to the wrist - Parks, Natalie E.; Morris, Stephen F. (DALHOUSIE MEDICAL JOURNAL, 2009)
Hand amputation is a devastating injury which may result in permanent quality-of-life impairment. The goal of treatment is to anatomically restore the amputated limb in order to optimize sensation and range of motion of the injured structures. All cases should be emergently referred to a hand surgeon trained in microsurgery for assessment and management. Generally accepted indications for replantation include amputation at the level of the wrist or mid-palm, thumb or multiple digit amputation and single digit amputation when distal to flexor digitorum superficialis insertion. In addition, replantation should always be attempted for children. Appropriate primary care which includes wrapping the amputated part in saline-soaked gauze, sealing in a plastic bag, and immersing in an ice bath increases the viability of amputated tissue and facilitates replantation. This review explores hand amputation classification, indications for replantation, primary care of the amputated part, surgical replantation techniques, post-operative care, and complications following replantation surgery. Three cases, treated at the Halifax Infirmary, were identified to illustrate the clinical presentation and outcome of patients presenting with multiple digit, thumb, or mid-palm amputation.